Maputo’s coastline in mutation. Current infrastructure impacts in Costa do Sol’s landscape - Beja da Costa, Ana (2021)
Costa do Sol coastal plains were Maputo’s last non-urbanized area and are now rapidly changing. The new Circular de Maputo (Maputo ringroad) blocks natural water flows, compromising the mangrove ecosystems while opening the way for this to become Maputo’s next urbanized area. The article analyzes the impacts of the Circular on Costa do Sol’s original landscape and provides a discussion based on the opportunities that such infrastructure offers or denies to the city, as on the meaning of its natural capital as part of the city’s green infrastructure